PHASE ANALYSIS OF NITI WIRE BASED ON SYNCHROTRON 2D X-RAY DIFFRACTION PATTERN IN MATLAB - Martin Dudr; Daniel Šimek; Jan Drahokoupil (Acta Polytechnica CTU Proceedings)
This paper deals with simplified phase analysis of 2D diffraction patterns obtained using microfocused X-ray at various places of superelastic NiTi wire under combined load. For this purpose, MATLAB routines and functions were created, which carry out integration of the patterns in various sectors of Debye ring, fitting of the patterns by a mixture of austenite and martensite (having neglected the R-phase) and successive evaluation of the quantitative phase content. The most crucial simplificating assumptions were: the neglection of the R-phase and the assumption of a) fibre texture or b) no texture.